Going the distance: information diffusion and influence dynamics of climate science on twitter - Setiawan, MM (2021)
An increasing distrust in scientists and experts has led to the polarisation of science. While there is a strong scientific consensus on human-induced global warming, ideological differences have led to public uncertainty around climate change and the polarisation of acceptance and rejection of the scientific authority. Climate change policies and net zero-emission goals become sources of contentious debates in the public, where the scientific evidence of climate change and the reliability of the science community are questioned. This has led to climate misinformation driven by the information asymmetry between climate experts and the public, which are further exacerbated by distortions of scientific framing in the media, or by the climate change countermovement.